Educação ambiental na escola: conscientização da necessidade de proteção da camada de ozônio - Silva, Givaldo Pereira da (2014)
While much has been written and spoken about the major problems of mankind, caused by overpopulation and for damage arising from an industrial age very developed, but each person has a different view of what's happening with the environment. Because this work is proposed to study the "environmental education in school: awareness of the need for protection of the ozone layer", intending to remedy the lack of information on the main causes of the destruction of the ozone layer and its aftermath. The main objective was to develop educational activities together students of 3rd grade of high school of the State College in the municipality of Staff Pedro Ribeiro Catu in Bahia, on environmental issues and problems, more specifically the problems of the ozone layer, through active methods, lecture, booklets, etc, making the students of need for ozone layer protection. Where it is found that the environmental education in school is today the very effective instrument to create and implement sustainable forms of society-nature interaction. This is the way for each person to change his habits and assume new attitudes that lead to the reduction of environmental degradation, which promote the improvement of quality of life and reduce the pressure on environmental resources.